2021
DOI: 10.1371/journal.pone.0254494
|View full text |Cite
|
Sign up to set email alerts
|

“Existimos”: Health and social needs of transgender men in Lima, Peru

Abstract: Background The health of transgender men (trans men)–individuals who identify as men and were assigned a female sex assigned at birth–is overlooked globally. This mixed-methods exploratory study sought to understand the lived experiences, health, and social needs of trans men in Lima, Peru to bring visibility to specific health needs and inform responsive and holistic public health efforts. Methods Between July 2016-January 2017, 46 trans men in Lima, Peru participated in a mixed-methods study. Four focus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Lack of access to appropriate and affordable health care can lead to a greater reliance on informal knowledge systems. This includes information about self-administration of hormones, which, in many cases, is undertaken without necessary medical monitoring or supervision (e.g., Do et al., 2018 ; Liu et al., 2020 ; Rashid et al., 2022 ; Reisner et al., 2021 ; Winter & Doussantousse, 2009 ).…”
Section: Chapter 2 Global Applicabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of access to appropriate and affordable health care can lead to a greater reliance on informal knowledge systems. This includes information about self-administration of hormones, which, in many cases, is undertaken without necessary medical monitoring or supervision (e.g., Do et al., 2018 ; Liu et al., 2020 ; Rashid et al., 2022 ; Reisner et al., 2021 ; Winter & Doussantousse, 2009 ).…”
Section: Chapter 2 Global Applicabilitymentioning
confidence: 99%
“…While overall health care services are diverse across the world (in terms of availability, accessibility, and quality), those services available to TGD people are often inadequate. Numerous reports from diverse regions worldwide show, while TGD people may report positive health care experiences, many others do not (e.g., Callander et al., 2019 ; Costa, da Rosa Filho et al., 2018 ; Do et al., 2018 ; Gourab et al., 2019 ; Health Policy Project et al., 2015; Liu et al., 2020 ; Motmans et al., 2017 ; Muller et al., 2019; PAHO, 2014 ; Reisner et al., 2021 ; Strauss et al., 2017 ; TGEU, 2017 ). Mainstream health care options often do not meet their needs for general, sexual, or gender-affirming health care.…”
Section: Chapter 2 Global Applicabilitymentioning
confidence: 99%
“…In addition, it is important to consider that each TM has different needs and characteristics, similar to what was reported by Peruvian TM in a recent study in which the diverse needs of TM and the social complexity they face are reported. 40 Therefore, it should not be assumed that everyone has initiated or wishes to initiate medical TP. Likewise, it is necessary to consider that the needs of individuals go beyond interventions of this type, so that care should be comprehensive and consider multiple aspects of their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the data on the relationships between sociodemographic variables and health conditions/situations of the participants with the PHC quality scores generated by them signal the importance of rescuing and applying references such as the social determination of health-disease as possible explanatory models for LGBTQIAP+ health and its interfaces. A study conducted in a South American country with trans men about their social and health needs described health as multidimensional and influenced by social, economic, and legal contexts, including family, school, employment and work, legal identity recognition, discrimination in public spaces and peer support 28 .…”
Section: Phc Quality and Associated Factorsmentioning
confidence: 99%